Intestinal microbiota and health - Kamer Kalip; Nazlı Atak (Turkish Society of Public Health Specialists, 2018)
Each organ has a unique microbiota, formerly known as its flora. In discussions around microbiota, intestinal microbiota comes to mind first. Microbes in the intestinal microbiota are essential for shaping and maintaining human physiology, and play an active role in hemostasis. As the gastrointestinal system holds a lot of bacteria and neurons, it is often called the second brain. The gastrointestinal microbiota is formed in utero and is influenced by various environmental factors. It influences the functioning of the immune system, as well as affecting the regulation of the metabolism. In this context, the gastrointestinal microbiota is implicated in some types of cancer, type 2 diabetes and Alzheimer's disease. It is thought that dysbiosis plays a part in the occurence of certain diseases. Therefore, it might be possible to prevent some diseases via the introduction of certain interventions. Further studies are needed in this field.